2021
DOI: 10.1161/hypertensionaha.120.15070
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MicroRNA-192-5p, a Downstream Effector of NOXs (NADPH Oxidases), Reverses Endothelial DHFR (Dihydrofolate Reductase) Deficiency to Attenuate Abdominal Aortic Aneurysm Formation

Abstract: We have shown that endothelial-specific DHFR (dihydrofolate reductase) deficiency underlies eNOS (endothelial NO synthase) uncoupling and formation of abdominal aortic aneurysm (AAA). Here, we examined a novel role of microRNA-192-5p in mediating NOX (NADPH oxidase)-dependent DHFR deficiency and AAA formation. microRNA-192-5p is predicted to target DHFR. Intriguingly, homo sapiens–microRNA-192-5p expression was substantially upregulated in human patients with AAA. In human aortic endothelial cells exposed to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…Primary bovine aortic endothelial cells (BAECs, Genlantis, passage 4 to 6) were cultured in M199 supplemented with 10% fetal bovine serum (FBS), 1% vitamin, and 1% l -glutamine as previously described [ [36] , [37] , [38] , [39] ]. Primary human aortic endothelial cells (HAECs, Lonza, passage 4 to 6) were cultured in EGM-2 media supplemented with 10% fetal bovine serum and EGM-2 SingleQuots (#CC-4176, Lonza) as previously reported [ 40 ]. Confluent BAECs were starved overnight with 5% FBS in M199 and treated with different concentrations of cigarette smoke extract (CSE, 0, 2.5%, 5%, 10%), recombinant human interleukin-6 (IL-6, 100 ng/mL, #206-IL-010, R&D), or recombinant SARS CoV-2 Spike protein (S protein, 500 ng/mL, #10549-CV-100, R&D) for 24 hrs before harvested for the following experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Primary bovine aortic endothelial cells (BAECs, Genlantis, passage 4 to 6) were cultured in M199 supplemented with 10% fetal bovine serum (FBS), 1% vitamin, and 1% l -glutamine as previously described [ [36] , [37] , [38] , [39] ]. Primary human aortic endothelial cells (HAECs, Lonza, passage 4 to 6) were cultured in EGM-2 media supplemented with 10% fetal bovine serum and EGM-2 SingleQuots (#CC-4176, Lonza) as previously reported [ 40 ]. Confluent BAECs were starved overnight with 5% FBS in M199 and treated with different concentrations of cigarette smoke extract (CSE, 0, 2.5%, 5%, 10%), recombinant human interleukin-6 (IL-6, 100 ng/mL, #206-IL-010, R&D), or recombinant SARS CoV-2 Spike protein (S protein, 500 ng/mL, #10549-CV-100, R&D) for 24 hrs before harvested for the following experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Electron spin resonance (ESR) was used as a gold standard to examine superoxide aninon production and eNOS uncoupling activity as we previously published [19 , 21 , 22 , 24 , 25 , [27] , [28] , [29] , [30] , [31] , [32] , [40] , [41] , [42] , [43] ]. Under normal conditions when eNOS is coupled, the addition of the NOS inhibitor l -NAME will increase the measured superoxide production, as eNOS is producing NO to scavenge superoxide; however, when eNOS is uncoupled and producing superoxide, its inhibition will lead to a decrease in measured superoxide.…”
Section: Resultsmentioning
confidence: 99%
“…Cryostat transverse cuts (5 μm) of lung sections were freshly prepared at -20°C. Levels of ROS in mouse lungs were determined using dihydroethidium (DHE) fluorescent imaging as we previously published [ 19 , 39 , 40 ]. DHE stock solution was prepared by dissolving DHE (MilliporeSigma, Cat# D7008, St. Louis, MO, USA) in dimethylsulfoxide (DMSO) at a concentration of 2 mM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the activation of Nrf2/HO-1/HIF-1α axis could upregulate the VEGF expression ( Li et al, 2016 ; Huang et al, 2018 ). Unfortunately, oxidative stress is generated at the injury site under the conditions of oxidative phosphorylation, which is detrimental to endothelial cells ( Huang K. et al, 2021 ). Hence, protecting endothelial cells against oxidative stress is crucial and urgent for the skin flap viability.…”
Section: Introductionmentioning
confidence: 99%